PENGARUH ETIKA PROFESI, PROFESIONALISME, KOMPETENSI DAN PELATIHAN AUDITOR TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK - Tercin, Kristiana; Sulistyo, Sulistyo; Sari, Ati Retna (Jurnal Riset Mahasiswa Akuntansi, 2017)
Auditor performance is the result of work that has been achieved by a public accountant on checking theclient's financial statements, to determine whether the financial statements are presented fairly or not.Professional ethics, professionalism, competence, and auditor training are very supportive in improvingauditor performance.The purpose of this study is to examine and explain: the influence of professional ethicson auditor performance, the effect of professionalism on auditor performance, the effect of competence onauditor performance, the effect of auditor training on auditor performance, influence, professionalism,competence, and auditor training simultaneously on auditor performance.This type of research used in thisresearch is explanatory research. The respondent in this study is an auditor who works at Malang PublicAccounting Firm. Purposive sampling technique with a total sample of 67 respondents